Alejo Carpentier and Julio Cortázar: Playing Seriously - Elena V. Ogneva (Литература двух Америк)
The essay is dedicated to the 120th birthday of the classic of Cuban literature Alejo Carpentier and the 110th birthday of the prominent Argentine writer Julio Cortázar. Despite the fact that they belonged to different generations, these like-minded writers, creators of the new Latin American novel, had much in common. Their interest in the fantastic serves as their shared artistic orientation in the essay, although the very nature of the fantastic in these writers’ works is completely different: in case of Carpentier, the founder of magical realism, we are talking about his formula of lo real maravilloso, rooted in the reality of the continent; as for Cortázar, one is faced here with his individual intellectual mythologizing. However, despite the differences in their poetics, both writers were united by the polemical intensity of their manifestos and interviews, both fought for the marvelous and the fantastic in literature as opposed to all sorts of cliches, banalities, snobbish prejudices, and literary fashion. For example, both received a creative impulse — each in his own way — by recoding and rearranging reminiscences and quotations from André Breton's Surrealist Manifesto. Defending their artistic principles and political convictions, both writers “played seriously”, as Cortázar said, and it is as evidenced by the examples of what they created “on a bet”.